Strategi Pemasaran dan Packaging Produk Olahan Ikan Bandeng melalui Program UMKM IKBAN Tahun 2024 - Moh. Ari Wibowo; Bariqoh, Asri; Rukmania Risqi; Afnan (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
The 2024 IKBAN MSME Program is a strategic initiative in developing marketing and packaging for Micro, Small and Medium Enterprises (MSMEs) in the milkfish sector. This program aims to increase the competitiveness and market penetration of milkfish products through a holistic and integrated approach. The marketing strategy is carried out through digital platforms and developing marketing campaigns through the use of social media by providing descriptions and advantages and benefits of milkfish. The IKBAN MSME program combines innovative digital marketing strategies and improving packaging quality. Attractive packaging designs are developed to increase the attractiveness of the product in the packaging. This program is expected to provide significant encouragement for MSMEs in the milkfish sector to achieve sustainable growth and expand their market share. The success of this program can have a positive impact not only on MSMEs but also on the fishing industry as a whole, encouraging local economic growth and increasing the competitiveness of milkfish products in domestic and international markets.